Pengaruh Aplikasi Palm Oil Mill Effluent (POME) Terhadap Indeks Kualitas Tanah dan Produktivitas Kelapa Sawit (Elaeis guineensis Jacq.) - Syahdina Atiyyah Dinata; Iwan Saputra; Boy Riza Juanda (Universitas Teuku Umar, 2026)
Oil palm (Elaeis guineensis Jacq.) is one of Indonesia’s most important plantation commodities, and the application of Palm Oil Mill Effluent (POME) has been increasingly adopted to support sustainable production. This study aimed to evaluate the effect of land application of POME on the Soil Quality Index (SQI), analyze the relationship between soil quality and oil palm productivity, and compare oil palm yields between POME-applied and non-applied areas at PTPN IV Regional II, Langkat Oil Palm Estate, North Sumatra. The research was conducted from March to April 2025 using a survey method with descriptive analysis. Soil samples were collected purposively from two POME pumping blocks (O and W) at depths of 0–30 cm and 60–90 cm, and analyzed for physical and chemical soil properties. The results showed that land application of POME significantly improved the Soil Quality Index, indicated by increased soil pH, organic carbon, total nitrogen, and available phosphorus, as well as decreased bulk density, particularly on undulating land. A positive relationship was observed between soil quality and oil palm productivity, and POME-applied areas consistently produced higher yields than non-applied areas. These findings demonstrate that land application of POME effectively enhances soil quality and increases oil palm productivity.Keywords : Oil palm, Palm Oil Mill Effluent (POME), Land application, Soil quality index, Productivity